Evaluation of wound healing activity of henna, pomegranate and myrrh herbal ointment blend - Ehab M. Elzayat; Sayed H. Auda; Fars K. Alanazi; Mohamed H. Al-Agamy (Elsevier, 2018)
This study assessed the wound healing potential and antimicrobial activity of henna, pomegranate and myrrh extract formulations and their blend in excision, and dead space wound models in rats in comparison to a marketed ointment (gentamycin). The natural extracts were used in ointment formulations alone or in a combination of three extracts at a total concentration of 15% w/w in medications. The percent of wound contraction in case of henna, myrrh, pomegranate, the blend and gentamycin (10 mg/kg) were 85.90-98.5%, 88.35-99.52%, 93.55-100%, 97.30-100%, and 90.25-100% from days 16 to 20, respectively. The blended formulation showed the highest increase in the percent of wound contraction and decrease in the epithelisation period compared to other formulations and showed comparable results to the standard ointment. The histological studies of excision biopsy at day 24 showed healed skin structures with normal epithelisation, the restoration of adnexa and fibrosis within the dermis in all of the formulation- and gentamycin-treated groups while the control group lagged behind in the formation of the amount of ground substance in the granulation tissue. The formulations showed antimicrobial activity against Candida, Staphylococcus aureus, mucous membrane infections and E. coli topical infections. The study proved the wound healing potential and antimicrobial activity of the herbal extract. Keywords: Wound healing, Henna, Pomegranate, Myrrh, Hydrophilic ointment, Herbal extract